2009
DOI: 10.1111/j.1749-7345.2009.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

The Larval Development, Metamorphosis and Juvenile Growth of the Turban Snail Lithopoma (Astraea) undosa (Wood, 1828) (Gastropoda:Turbinidae)

Abstract: This work presents the embryonic, larval, and postlarval development of Lithopoma undosa (L. undosa) (20 ± 2 C and the effect of natural inducers on the larval metamorphosis. Embryonic development until hatching of the trochophore larva took 15 h. Early veliger larvae with well‐developed shell were after 24 h. At 48 h, the operculum was completely formed. Cephalic tentacles were visible after 72 h. Larvae reached competence 6 to 7 d after fertilization, and was characterized by the presence of branched cephali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
2
3
0
1
Order By: Relevance
“…The mean growth rate of C. pica larvae in this study (34 μm/day) was higher or similar to those reported in other vetigastropods with lecitotrophic larva such as Astraea undosa Wood 1828 (9 μm/day; Salas‐Garza, Parés‐Sierra, Gómez‐Rigalt, & Carpizo‐Ituarte, ), Haliotis sorenseni Bartsch 1940 (25 μm/day; Leighton, ), 2), Tegula rustica (Gmelin 1791) (8 μm/day; Kulikova & Omel'yanenko, ) and T. niloticus (35 μm/day; Hahn, ). Conversely, the mean final survival of C. pica (8%) was comparatively lower than those reported for Calliostoma ligatum Gould 1849, (90%; Holyoak, ), Haliotis mariae Wood 1828 (51%; Al‐Rashdi & Iwao, ), H. asinina (40%; Chaitanawisuti et al., ).…”
Section: Discussionsupporting
confidence: 86%
“…The mean growth rate of C. pica larvae in this study (34 μm/day) was higher or similar to those reported in other vetigastropods with lecitotrophic larva such as Astraea undosa Wood 1828 (9 μm/day; Salas‐Garza, Parés‐Sierra, Gómez‐Rigalt, & Carpizo‐Ituarte, ), Haliotis sorenseni Bartsch 1940 (25 μm/day; Leighton, ), 2), Tegula rustica (Gmelin 1791) (8 μm/day; Kulikova & Omel'yanenko, ) and T. niloticus (35 μm/day; Hahn, ). Conversely, the mean final survival of C. pica (8%) was comparatively lower than those reported for Calliostoma ligatum Gould 1849, (90%; Holyoak, ), Haliotis mariae Wood 1828 (51%; Al‐Rashdi & Iwao, ), H. asinina (40%; Chaitanawisuti et al., ).…”
Section: Discussionsupporting
confidence: 86%
“…The embryonic development of C. pica described in this study was very similar to that previously reported for this species (Bell, 1992), as well as for other vetigastropods such as Calliostoma ligatum (Holyoak, 1988), H. discus hannai (Hanh, 1989b), H. tuberculata coccinea (Courtois De Viçose et al, 2007), H. varia (Najmudeen and Victor, 2004), Lithopoma undosa (Salas-Garza et al, 2009), Tegula eiseni (Guzmán del Próo et al, 2011), Tegula funebralis (Moran, 1997), T. rustica (Kulikova and Omel'yanenko, 2000) and T. niloticus (Heslinga and Hillmann, 1981). However, new details about the development of C. pica such the segmentation process and the formation of larval specific structures such as the retractor muscle, integumental attachment, epipodial tentacles, apophysis on the propodium, otolith, snout protrusion, cephalic tentacles and its tubules are included in this study.…”
Section: Early Ontogenetic Developmentsupporting
confidence: 88%
“…The rate of development of C. pica was lower than that of other tropical species such as H. asinina, H. ovina (Jarayabhand and Paphavasit, 1996) and T. niloticus (Heslinga and Hillmann, 1981), where crawling veliger larvae appear before 3 days. However, the C. pica development rate was higher than that of temperate and subtropical species such as Crepidula fornicata (Pechenik, 1984), H. corrugata (Leighton, 1974), H. midae (Genade et al, 1988), H. mariae (Al-Rashdi and Iwao, 2008), H. tuberculata (Koike, 1978), Gibbula cirenaria (Underwood, 1972), L. undosa (Salas-Garza et al, 2009), T. eiseni (Guzmán del Próo et al, 2011), T. funebralis (Moran, 1997) and T. rustica (Kulikova and Omel'yanenko, 2000), where crawling larvae developed 4 days after fertilization.…”
Section: Early Ontogenetic Developmentmentioning
confidence: 95%
“…Therefore, the term ‘settled’ or ‘settlers’ should only be considered after the shedding of the velum with the consequent loss of the ability to swim, as occurred at the early postlarval stage. Velum shedding is one of the characteristics used to describe the onset of metamorphosis in abalone (Searcy-Bernal et al ., 1992; Roberts & Nicholson, 1997; De Viçose et al ., 2010) and other marine gastropods (Zhao & Qian, 2002; Salas-Garza et al ., 2009; Ferranti et al ., 2021). Limpets in the early postlarval stage develop into juveniles, characterized by a well-developed crescent-moon shaped teleoconch and active grazing behaviour.…”
Section: Discussionmentioning
confidence: 99%